The Effect of Isometric Exercise on Changes in Pain and Functional Activity in Osteoarthritis Knee Patients at Samarinda Class IV Hospital - Sulfandi, Sulfandi; Azizan, Noor Azliyana; Rosyida, Dwina (Champions: Education Journal of Sport, Health, and Recreation, 2025)
Osteoarthritis of the knee is a degenerative disease that directly impacts joint cartilage, characterized by pain and stiffness, causing a decrease in function and quality of life of sufferers. This study aimed to determine the effect of giving isometric exercise on pain and functional activity changes in patients with knee osteoarthritis at Hospital Level  IV in Samarinda.  This study used a pre-experimental method with a pre-test and post-test one-group design approach. Seventeen knee osteoarthritis respondents with pain and functional activity disturbances were given an isometric exercise with a frequency of three times a week for one month. The measurement tool used to evaluate pain and functional activity was the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). The statistical test using the paired sample t-test showed that p <0.05 indicated that giving isometric exercise affected in pain and functional activity changes in patients with knee osteoarthritis at  Hospital Level IV in Samarinda, then H0 was rejected, and Ha was accepted. This indicates that giving isometric exercise affects changes in pain and functional activity in osteoarthritis knee at Hospital Level IV in Samarinda.